DISIPLIN SHALAT JAMAAH PARA PEDAGANG MUSLIM DI PUSAT NIAGA PALOPO - Mahmud, M. Said (IAIN Palopo, 2017)
This research is a qualitative research that discusses the issue of commitment among Muslim traders at the Center of Commerce Palopo on pray congregationally. The main issue discussed in this research is whether there is a commitment among Muslim traders at Palopo Trade Center in the implementation of pray congregationally?, and if any, how far is the effect of such disciplinary commitment in establishing silaturrahim and in improving their business result as a trader? The results showed that the implementation of the congregational prayers performed by traders at the Palopo Trading Center can be categorized as part of the factor of the formation of integration behavior, this is supported by the commitment and discipline. Discipline in prayer congregation for traders Palopo City Commercial Center against work ethic is done by: get used to unite and help; perfecting the prayers of the less worshipers; gain the good of the world; enliven sense of equality and brotherhood; familiarize people with their leaders; gain the good of religion; helps concentration of mind.